Student’s perception on community pediatric rotation quality - Reátegui Guzmán, Luis Américo (2013)
Introduction: Published research on university education quality of service has focused on course content and submission and not on the quality of service. The instrument used for measuring quality is the SERVQUAL model. Objectives: To determine the quality of education in Community Pediatrics rotation from the student’s perspective. Design: Cross-sectional, descriptive, quantitative study. Location: Department of Pediatrics, San Fernando School of Medicine, Universidad Nacional Mayor de San Marcos. Participants: University Pediatrics rotation students. Interventions: SERVQUAL survey application before and after rotation. Results: Overall satisfaction for all dimensions was found and severe unsatisfaction was minimal. In size classes, teachers, facilities, staff, information, communication with the university and institutional environment unsatisfaction was median with importance given to educational service. Satisfaction was encountered in the other dimensions. Dimensions facilities, social life, administrative personal, communication with the university, financial and institutional environment showed low levels of severe unsatisfaction. Conclusions: Most students had overall satisfaction, median satisfaction, with satisfaction in permanency, rotation, performance and health during rotation of Community Pediatrics; more important attributes given by the pupils were quality of classes and teachers’ capacity for teaching.